Comparison of corrected serum calcium changes following thyroid and non thyroid neck surgeries - Sinha, Saloni; Baskota, Dharma Kanta (Nepalese Journal of ENT Head and Neck Surgery, 2018)
Objective: To compare the corrected serum calcium changes following thyroid and non thyroid neck surgeries.Material and Methods: It was a prospective, longitudinal and comparative study, done in Ganesh Man Singh Memorial Academy of ENT and Head and Neck Studies, Tribhuvan University, Teaching hospital, Kathmandu, Nepal. Convenient sample size was taken of patients undergoing thyroid and non thyroid neck surgeries under general anaesthesia, between 1st November 2009 to 30th April 2011.Result: Total 87 cases were included which comprises 41 cases of thyroid and 46 cases of non thyroid neck lesions. Total females in thyroid cases were 39 out of 41 and in non thyroid cases 25 out of 46. The mean corrected calcium in thyroid cases were 2.04 ± 0.07, 1.75 ± 0.26, 1.92 ± 0.16 and 2.00 ± 0.07 in pre-operative, recovery room (immediate post-operative), post-operative day-1(POD 1) and post-operative day-4(POD- 4) respectively. The mean calcium changes in non thyroid cases were 2.04 ± 0.09, 1.89 ± 0.19, 1.94 ± 0.13 and 1.99 ± 0.04 in pre-operative period, recovery room (immediate post-operative), post-operative day-1(POD-1) and post-operative day-4 (POD- 4) respectively. In both thyroid and non thyroid group, the calcium drop was statistically significant  (< 0.05) in recovery. Rest were not significant statistically. The mean differences from pre-operative to recovery and preoperative to POD-1 corrected calcium changes were also significant in both thyroid and non thyroid groups. The mean difference between preoperative to POD-4 was not significant in both groups.Conclusion: After comparing the corrected serum calcium changes following thyroid and non thyroid neck surgeries, the transient post-operative hypocalcaemia is not a thyroid surgery dependent phenomenon. Haemodilution is the main factor for hypocalcaemia in immediate postoperative period in all major neck surgeries.Nepalese Journal of ENT Head and Neck Surgery, Vol. 6, No. 1, 2015